Genetic diversity of 40 genotypes of cape gooseberry Physalis peruviana L. using microsatellite markers - Delgado-Bastidas, Nataly; Lagos-Santander, Liz K; Lagos-Burbano, Tulio César (Revista de Ciencias Agrícolas, 2019)
Physalis peruviana L., also called cape gooseberry, is widely known for its nutraceutical and economic importance. However, little is known about the genetic diversity of this species at the molecular level, mainly due to its status as an orphan species. Therefore, knowledge of the genetic diversity of germplasm collections of P. peruviana will allow determining the level of genetic variability that is available to breeders for selection processes. This study assessed the genetic variation present in 40 cape gooseberry genotypes using six SRR (simple sequence repeats) molecular markers selected based on their high polymorphism in P. peruviana L. The collection was divided into three populations: DH (double haploid lines), FT (Fusarium oxysporum-tolerant genotype), and UDENAR (Universidad de Nariño). We detected 7.33 alleles using GenAlex v. 6.5 and Arlequin 3.5.2 software. Among the six markers used, SSR15 and SSR138 were the most informative. Together, these markers indicated that 22.2% of loci were polymorphic with an average expected heterozygosity of 0.09, which is considered low. The AMOVA showed that the variance within genotypes contributes to 100% of the total variance, indicating the absence of population structure. Overall, we conclude that the level of variability among genotypes is low.